2009
DOI: 10.1111/j.1471-4159.2009.06419.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative positioning of diazepam in the benzodiazepine‐binding‐pocket of GABAA receptors

Abstract: GABA A receptors are the major inhibitory neurotransmitter receptors in the brain. Some of them are targets of benzodiazepines that are widely used in clinical practice for their sedative/hypnotic, anxiolytic, muscle relaxant and anticonvulsant effects. In order to rationally separate these different drug actions, we need to understand the interaction of such compounds with the benzodiazepine-binding pocket. With this aim, we mutated residues located in the benzodiazepinebinding site individually to cysteine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 34 publications
3
30
0
8
Order By: Relevance
“…Although Brflurazepam occupies a pocket that resembles the location of the α/γ interface in GABA A receptors, the bromine substituent on position 7 of the phenyl moiety in flurazepam points out of the benzodiazepine pocket in ELIC. In contrast, previous photolabeling studies with flunitrazepam (44) or experiments with isothiocyanate substitutions at position 7 of diazepam (45,46) position this moiety near α1H101 of loop A in GABA A receptors, a location deep inside the pocket (I79 in ELIC). Presumably, the divergent amino acid composition between ELIC and the high-affinity α/γ benzodiazepine site in GABA A receptors causes differences in the pocket architecture and results in different benzodiazepine-binding poses in ELIC.…”
Section: +mentioning
confidence: 63%
“…Although Brflurazepam occupies a pocket that resembles the location of the α/γ interface in GABA A receptors, the bromine substituent on position 7 of the phenyl moiety in flurazepam points out of the benzodiazepine pocket in ELIC. In contrast, previous photolabeling studies with flunitrazepam (44) or experiments with isothiocyanate substitutions at position 7 of diazepam (45,46) position this moiety near α1H101 of loop A in GABA A receptors, a location deep inside the pocket (I79 in ELIC). Presumably, the divergent amino acid composition between ELIC and the high-affinity α/γ benzodiazepine site in GABA A receptors causes differences in the pocket architecture and results in different benzodiazepine-binding poses in ELIC.…”
Section: +mentioning
confidence: 63%
“…Direct apposition of the reactive group and cysteine leads to a covalent reaction. From this work, we know that the C1 atom of diazepam is located close to ␣ 1 His-101 (75) and that the 3Ј-atom is located close to ␣ 1 Ser-205 and ␣ 1 Thr-206 (76). Very recently, diazepam has been docked into a multitude of conformational variants of a large number of homology models of the GABA A receptor, and the docking poses were rated according to all available experimental observations (77).…”
Section: Modulation Of Gaba a Receptorsmentioning
confidence: 99%
“…3-NCS was able to displace [ 3 H]Ro15–1788 or [ 3 H]flunitrazepam from wild-type α 1 β 2 γ 2 receptors. The K i values were 340±16 nM and 240±55 nM [32], respectively. The K i values for displacement of [ 3 H]Ro 15–1788 by 3-NCS in α 2 β 2 γ 2 were 1550±250 nM (n = 3) and in α 5 β 1 γ 2 receptors 9840±1480 nM (n = 3).…”
Section: Resultsmentioning
confidence: 93%
“…Diazepam is arranged in the binding pocket of α 1 β 2 γ 2 receptors such as to allow interaction of a reactive group replacing the –Cl atom with a reactive residue in place of α 1 H101 [28][31] and interaction of a reactive group attached to the 3′-atom with a reactive residues in place of α 1 S205 or α 1 S206 [32]. It has also been shown that a reactive residue in place of the –Cl atom interacts with a reactive residue in place the histidine homologous to α 1 H101 in α 2 , α 3 and the corresponding arginine residue in α 6 but not to the histidine residue in α 5 [33].…”
Section: Introductionmentioning
confidence: 99%